Mangrove Conservation in Macao SAR, China: The Role of Environmental Education among School Students - Tagulao, Karen Araño; Bernardo, Allan B. I.; Kei, Loi Hoi; Calheiros, Cristina Sousa Coutinho (International Journal of Environmental Research and Public Health, 2022)
Mangrove forests are one of the most ecologically valuable ecosystems in the world and provide a wide variety of ecosystem services to coastal communities, including cities. Macao, a highly urbanized coastal city located on the southern coast of China west of the Pearl River, is home to several species of mangroves with many associated flora and fauna. Mangrove forests in Macao are vulnerable to threats due to pressure from rapid and massive urban developments in the area, which led to mangrove loss in the past decades. To address this issue, the local authorities established special Ecological Zones for the management of the local mangroves. To reinforce local conservation efforts, educating the local population about the value of mangroves, especially school students, is of utmost importance. To evaluate the impact of environmental education activities on the environmental orientation, knowledge, and values of students toward mangrove conservation in Macao, a quasi-experimental study was undertaken. The effectiveness of a mangroves exhibition and field visit were evaluated using the New Environmental Paradigm (NEP) Scale—Macao version in a group of local school students who participated in the activities. Overall, the results provided consistently positive evaluations of the impact of the environmental education program. The strongest improvements were found in the students’ pro-environmental orientations, knowledge about mangroves, and value for environmental protection.
0 citations (Crossref) [2023-03-15] Number: 6
Keywords: NEP-New Ecological Paradigm; conservation; environmental orientation; environmental protection; urban mangroves

The Status of Mangroves in Macao and the Efficacy of Localized Environmental Educational Intervention on School Students' Environmental Knowledge - Loi Hoi Kei (University of Saint Joseph, 2020)
Keywords: Master of Environmental Sciences and Management (MESM); University of Saint Joseph